Barriers to student active learning in higher education - Børte, Kristin; Nesje, Katrine; Lillejord, Sølvi (Teaching in higher education, 2023)
This article reviews research that consistently, across borders and over time, reveals inertia in Higher Education institutions related to innovation in academic teaching. Despite frequent calls for more student-active learning, studies find that teaching remains predominantly traditional and teacher-centred. While research is recognised as continuously developing, border-crossing, investigative and innovative collaborative activities that needs an infrastructure to succeed, the need for collaborative development and a supporting infrastructure is rarely mentioned in academic teaching, often described as individual and traditional in the research. To better understand this paradox, and to identify barriers to student active learning, we reanalysed articles from two systematic reviews, one on campus development and one on learning and teaching with technology. The article identified the following prerequisites for student active learning to succeed: (1) better alignment between research and teaching practices, (2) a supporting infrastructure for research and teaching, (3) staff professional development and learning designs.